Influence of printing direction on mechanical behavior of additively manufactured high strength low alloy steel - Hardi Pardi (Nanyang Technological University, 2020)
Additive manufacturing (AM) has been rapidly adopted by various industries to optimize their design and manufacturing processes. This includes the aerospace and medical industries. The marine and offshore industry, however, is relatively slower in accepting the AM technology. This is due to the reasons such as a lack of research on the quality and reliability of the products that are AMed using materials that are commonly used in the industry. This has caused a lack of confidence in the safety of the AMed products, leading to a reluctance in using them.